PEMBELAJARAN PRAKTEK ALAT MUSIK TRADISONAL KECAPI MAKASSAR PADA SISWA SMPN 49 MAKASSAR MELALUI METODE DARING - Pasyah, Soekarno B.; Kama, NurulInayah Anis (Manifestasi: Jurnal Pendidikan dan Pengajaran, 2022)
Music education for junior high school students has long been considered important, because apart from being educative it is also appreciative. Music education helps the development of students in the field of music, develops an attitude of respect and love for the nation's cultural works, and provides freshness and joy to students. In addition to achievement, it is also hoped that their participation in developing students' artistic and aesthetic sensitivity is also expected. Thus music education plays a role in the development of the personality of the subject-student. Many factors affect learning today, among others, online learning methods, which in general use the internet as the main material. The output that will be produced in the learning process of Kacapi traditional musical instruments for SMPN 49 children requires a special method besides the students being very difficult to digest the material and in terms of the internet network which is sometimes less stable, so it must be repeated in the delivery of material, especially in the field of practice. teachers must be able to respond to the current conditions by developing learning methods outside online.